Nonparametric estimates of productivity and efficiency change in Australian Broadacre Agriculture - Khan, F.; Salim, Ruhul; Bloch, Harry (Blackwell Publishing Asia, 2014)
This paper computes and decomposes Färe-Primont indexes of total factor productivity of Australian broadacre agriculture by estimating distance functions. Using state-level data from 1990 to 2011, the empirical results show that TFP grew at an average rate of 1.36 per cent per annum in the broadacre agriculture over the period 1990–2011. There are variations of total factor productivity (TFP) growth across states and fluctuations over time within each state and territory. However, overall, there is a clear movement towards slower TFP growth across the sample period. Further decomposition of TFP growth shows that it is declining growth in technical possibilities (technological progress) that is the main driver of the declining trend in productivity growth in broadacre agriculture in Australia.